Effect of Aluminum doping on the properties of magnetron sputtered ZnO films. (2016) - Krishna Kumar, M.; Deepak Raj, P.; Jeyadheepan, K.; Sridharan, M.
Abstract: Aluminum doped zinc oxide (AZO) thin films were coated on the glass substrate by diffusing the Al in to the sputtered ZnO thin films. Initially, zinc oxide (ZnO) thin films were deposited on glass substrates using reactive dc magnetron sputtering (DCMS) technique followed by Aluminum (Al) were deposited over the ZnO films by vacuum evaporation technique. The prepared samples were annealed at 400 °C for 3h in vacuum in order to diffuse Al uniformly in to ZnO matrix. The influence of Al doping over the micro-structure, surface morphology, optical and electrical properties of the films were studied by X-ray diffraction (XRD), field emission-scanning electron microscopy (FE-SEM), UV-Visible spectroscopy and four point probe (FPP) method respectively. Resistivity of the AZO films decreased with increase in the Al concentration and the film deposited with high Al concentration offered low electrical resistivity of ∼28 Ω.cm and optical bandgap of 3.21 eV.